Metal-insulator-metal nano square ring resonator for gas sensing applications. Issue 1 (2nd January 2021) - Butt, M. A.; Khonina, S. N.; Kazanskiy, N. L.
ABSTRACT: In this paper, three designs of Square Ring resonator (SRR) based on metal-insulator-metal (MIM) WG are reported. The transmission spectra and electric field distribution of the sensor structure are simulated using finite element method (FEM). The effect of structural parameters on the spectral characteristics and sensing performance are investigated comprehensively. The maximum achieved sensitivity and figure of merit of the sensor reached 1320 nm/RIU and 16.7, respectively. Due to the high performance and easy fabrication, this kind of plasmonic structures can find noteworthy applications in integrated optical circuits and on-chip nano-sensors.